Lower prevalence of carotid plaque hemorrhage in women, and its mediator effect on sex differences in recurrent cerebrovascular events. - Neghal Kandiyil; Nishath Altaf; Akram A Hosseini; Shane T MacSweeney; Dorothee P Auer (PLoS ONE)
Background and purpose Women are at lower risk of stroke, and appear to benefit less from carotid endarterectomy (CEA) than men. We hypothesised that this is due to more benign carotid disease in women mediating a lower risk of recurrent cerebrovascular events. To test this, we investigated sex differences in the prevalence of MRI detectable plaque hemorrhage (MRI PH) as an index of plaque instability, and secondly whether MRI PH mediates sex differences in the rate of cerebrovascular recurrence. Methods Prevalence of PH between sexes was analysed in a single centre pooled cohort of 176 patients with recently symptomatic, significant carotid stenosis (106 severe [≥70%], 70 moderate [50-69%]) who underwent prospective carotid MRI scanning for identification of MRI PH. Further, a meta-analysis of published evidence was undertaken. Recurrent events were noted during clinical follow up for survival analysis. Results Women with symptomatic carotid stenosis (50%≥) were less likely to have plaque hemorrhage (PH) than men (46% vs. 70%) with an adjusted OR of 0.23 [95% CI 0.10-0.50, P<0.0001] controlling for other known vascular risk factors. This negative association was only significant for the severe stenosis subgroup (adjusted OR 0.18, 95% CI 0.067-0.50) not the moderate degree stenosis. Female sex in this subgroup also predicted a longer time to recurrent cerebral ischemic events (HR 0.38 95% CI 0.15-0.98, P = 0.045). Further addition of MRI PH or smoking abolished the sex effects with only MRI PH exerting a direct effect. Meta-analysis confirmed a protective effect of female sex on development of PH: unadjusted OR for presence of PH = 0.54 (95% CI 0.45-0.67, p<0.00001). Conclusions MRI PH is significantly less prevalent in women. Women with MRI PH and severe stenosis have a similar risk as men for recurrent cerebrovascular events. MRI PH thus allows overcoming the sex bias in selection for CEA.